Contribution of Rare and Common Genetic Variants to Plasma Lipid Levels and Carotid Stiffness and Geometry. (August 2015) - Proust, Carole; Empana, Jean-Philippe; Boutouyrie, Pierre; Alivon, Maureen; Challande, Pascal; Danchin, Nicolas; Escriou, Guillaume; Esslinger, Ulrike; Laurent, Stéphane; Li, Zhenlin; Pannier, Bruno; Regnault, Veronique; et al.
<x xml:space="preserve">Abstract</x> Background— We assess the contribution of common and rare putatively functional genetic variants (most of them coding) present on the Illumina exome Beadchip to the variability of plasma lipids and stiffness of the common carotid artery. Methods and Results— Measurements were obtained from 2283 men and 1398 women, and after filtering and exclusion of monomorphic variants, 32 827 common (minor allele frequency >0.01) and 68 770 rare variants were analyzed. A large fraction of the heritability of plasma lipids is attributable to variants present on the array, especially for triglycerides (fraction of variance attributable to measured genotypes: V(G)/Vp=31.4%, P<3.1×10–11) and high-density lipoprotein cholesterol (V(G)/Vp=26.4%, P<4.2×10–12). Plasma lipids were associated with common variants located in known candidate genes, but no implication of rare variants could be established. Gene sets for plasma lipids, blood pressure, and coronary artery disease were defined on the basis of recent meta-analyses of genome-wide association studies. We observed a strong association between the plasma lipids gene set and plasma lipid variables, but none of the 3 genome-wide association studies gene sets was associated with the carotid parameters. Significant V(G)/Vp ratios were observed for external (14.5%, P<2.7×10–5) and internal diameter (13.4%, P<4.3×10–4), stiffness (12.5%, P<8.0×10–4), intima-media thickness (10.6%, P<7.9×10–4), and wall cross-sectional area (13.2%, P<2.4×10–5). A significant association was observed between the common rs2903692 polymorphism of the CLEC16A gene and the internal diameter (P<4.3×10–7). Conclusions— These results suggest an involvement of CLEC16A, a gene that has been reported to be associated with immune disorders, in the modulation of carotid vasodilatation.